All's Boman! - the cant lexis in London in 1725 - Hamilton, R (2010)
When Jack Sheppard embarked on his final journey from Newgate prison to be hanged at Tyburn in 1724, he became the focus of a highly disparate but closely related set of texts, some of which were written about him, while others emerged from the milieu in which he had cut a prominent figure. As a result, we have a stereoscopic perspective on the cant lexis of a particular time and place - London during some twenty years at the beginning of the eighteenth century. Directly connected with Sheppard were newspaper reports, poems, a pantomime, and an unperformed play, The Prison-Breaker. Further, these texts were bracketed by two dictionaries. The first, A new dictionary of the canting crew by B.E. in 1699, represented cant as it was about twenty years before Sheppard was hanged, while The New Canting Dictionary, published anonymously in 1725, incorporated terms new at the time of Sheppard's death. These two dictionaries coexist with works by Charles Hitchin, Daniel Defoe, John Poulter, and Anon, which contain cant glossaries seemingly independent of the dictionary tradition. We can trace the emergence of certain words which almost seem to define this moment - the Rumbo Ken, the running snabble, the Whit, and of course the Boman Prig, of which Sheppard was perhaps the fullest exemplar. This paper will examine the interaction between the dictionaries, dramas, prose narratives, and songs in order to shed light on both the dynamic of the presentation of cant in its written form, and the core of terms which are locacted in this particular time and place. We can even see the newspaper accounts of Sheppard's final capture transformed before our eyes into the cant speech of the time in "Frisky Moll's Song" as it is sung in Harlequin Sheppard only a week after Sheppard's death.